2010
DOI: 10.1007/s11764-009-0112-3
|View full text |Cite
|
Sign up to set email alerts
|

Social outcomes in young adult survivors of low incidence childhood cancers

Abstract: The study revealed important differences in social outcomes between survivors and controls early in adult life. Specific difficulties pertain to studying social status in early adulthood because of the natural transition characteristics for this age group. Therefore, longer follow-up is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 50 publications
1
27
0
1
Order By: Relevance
“…Dieluweit et al reported a higher proportion of adolescent cancer survivors who were employed compared to an age-matched sample from the general population [20]. Nevertheless, most of the published studies found the employment rate to be lower among childhood cancer survivors compared with the controls [6,13,[15][16][17][18]29]. However, some of these studies include survivors of childhood brain and central nervous system cancers, and the difference in employment rate with the controls disappears when those types of cancers are excluded [24,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dieluweit et al reported a higher proportion of adolescent cancer survivors who were employed compared to an age-matched sample from the general population [20]. Nevertheless, most of the published studies found the employment rate to be lower among childhood cancer survivors compared with the controls [6,13,[15][16][17][18]29]. However, some of these studies include survivors of childhood brain and central nervous system cancers, and the difference in employment rate with the controls disappears when those types of cancers are excluded [24,30].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning occupational outcomes, most of the studies conducted have reported higher rates of unemployment among childhood cancer survivors than among their siblings or the population as a whole [4,6,[13][14][15][16][17][18]. Factors found to be associated with unemployment risk in the survivor population are both demographic (current age, female gender, interrupted schooling, lower education) [16,17,19,20] and cancerrelated (younger age at diagnosis, treatment with cranial irradiation, somatic late effects) [13,14,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to various physical problems in childhood cancer survivors (CCSs) [3], social outcomes vis-à-vis marriage, education and employment are apparently affected by these late effects, either directly or indirectly. An increasing number of studies have focused on the social outcomes of CCSs [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the results of the Childhood Cancer Survivor Study (CCSS) suggest that CCSs generally have high school graduation rates similar to those in the general population, but they are slightly less likely to attend college; they are also more likely to be unemployed and not married as young adults [5]. Johannsdottir et al [6] also outline important differences in social outcomes (i.e., employment and parenthood) between CCS and controls early in adult life.…”
Section: Introductionmentioning
confidence: 99%
“…Also, data have been included in a Nordic study of the psycho-social effects of having had cancer during childhood 911…”
Section: Resultsmentioning
confidence: 99%